The Corinthian Isthmus between East and West (Aristonothos. Rivista di Studi sul Mediterraneo Antico, 2022)
Nel VII secolo a.C. Corinto è il punto di partenza di una nuova dinamica di scambi verso Occidente dal suo porto di Lechaion sul Golfo di Corinto. Analisi dei vari aspetti di tale dinamica nella fase precedente la costruzione del diolkos con la situazione particolare di Corinto su un istmo. Possibili interferenze con Atene. Contributo ad una lettura strutturale degli scambi mediterranei. In the 7th century BCE the port of Lechaion on the Gulf of Corinth is the starting point for a new trade dynamic towards the West. The various aspects of this dynamic in the phase before theconstruction of the diolko, with the particular siting of Corinth on an isthmus, are analysed. Possible interference with Athens and a contribution to a structural reading of Mediterranean trade are discussed.
Keywords: Trade; Corinth; Lechaion; diolkos; Athens; Solon; shipping routes; amphorae; pottery